Muslim Sanzijing shifts and continuities in the definition of Islam in China - Tontini, Roberta (China studies (Leiden, Netherlands), 2016)
Through a comprehensive study that includes a rigorous analysis of popular Chinese Islamic primers belonging to the Sanzijing tradition, Tontini offers fresh insights on the little known intellectual and legal history of Islam on Chinese soil to convincingly demonstrate its evolving quality in response to changing social norms.